STRES KERJA, KEPUASAN KERJA, KESEHATAN FISIK, KESALAHAN KERJA DAN KECELAKAAN KERJA TEKNISI PESAWAT UDARA - Saptono Widodo; M. As'ad Djalali (University of Merdeka Malang, 2011)
Abstract The study examines job stress, job satisfaction, physical health, work accidents and faulty work. Study was involving 100 aircraft technicians PT. Merpati Nusantara Airlines. Occupational injuries is measured by Safety Related Injuries Scale. Work was measured with a scale error faulty work by the job description of aircraft maintenance division that has been standard. Physical health was measured by Physical Health Questionnaire (PHQ). Job satisfaction was measured by job satisfaction scale developed by researchers. Work stress was measured by Job Stress Survey (JSS). Data occupational accidents, faulty work, physical health, job satisfaction and job stress were analyzed with statistical regression analysis. The analysis showed job stress did not predict an increase in accidents and faulty work. Job stress did not predict decline in physical health and job satisfaction. High and low occupational accidents, faulty work, physical health, and aircraft technician job satisfaction can not be predicted through the high and low job stress. Keywords: job stress, job satisfaction, physical health, work mistakes, work accident